1999
DOI: 10.1111/j.1532-5415.1999.tb02996.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Companion Animals on the Physical and Psychological Health of Older People: An Analysis of a One‐Year Longitudinal Study

Abstract: The results demonstrate the benefits of pet ownership in maintaining or slightly enhancing ADL levels of older people. However, a more complex relationship was observed between pet ownership and an older person's well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
195
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(214 citation statements)
references
References 26 publications
11
195
0
8
Order By: Relevance
“…From the focus group discussions there emerged such themes as physical stimulation from dog-walking, psychosocial benefits from contact with dogs, and dogs being seen as providers of safety, security, and protection (Knight and Edwards, 2008). These results are in line with categories in our study, and are further confirmed by a longitudinal study of almost a thousand participants aged ≥65 years, who completed a telephone-administered questionnaire (Raina et al, 1999). Raina et al (1999) concluded that companion animals helped maintain or enhance the physical health of older people and could also positively affect their psychological well-being.…”
Section: Perceiving Animals As Family Memberssupporting
confidence: 90%
“…From the focus group discussions there emerged such themes as physical stimulation from dog-walking, psychosocial benefits from contact with dogs, and dogs being seen as providers of safety, security, and protection (Knight and Edwards, 2008). These results are in line with categories in our study, and are further confirmed by a longitudinal study of almost a thousand participants aged ≥65 years, who completed a telephone-administered questionnaire (Raina et al, 1999). Raina et al (1999) concluded that companion animals helped maintain or enhance the physical health of older people and could also positively affect their psychological well-being.…”
Section: Perceiving Animals As Family Memberssupporting
confidence: 90%
“…17,32 Our study indicates that pet attachment levels in this community are very similar to the levels shown previously in the United States. 17,32 This high level of pet attachment was not expected, because we expected a more utilitarian view of dogs in the household.…”
Section: Discussionsupporting
confidence: 72%
“…17,32 Our study indicates that pet attachment levels in this community are very similar to the levels shown previously in the United States. 17,32 This high level of pet attachment was not expected, because we expected a more utilitarian view of dogs in the household. We identified that, for our pet owner cohort, pets play a role of emotional and social support in the elderly population and those individuals without extensive support networks, because increased pet attachment was associated with increased owner age and lower self-reported happiness.…”
Section: Discussionsupporting
confidence: 72%
“…Approximately 62% of households have at least one pet, and over half of these households have multiple pets (1). Various studies have demonstrated the importance of pets in overall health and well-being and for providing social support (2)(3)(4)(5). Consistent with this devotion to pets, owners in the United States spend approximately $10.94 billion annually on pet supplies and over-the-counter pet medications and $14.11 billion annually on veterinary care (1).…”
mentioning
confidence: 87%